Lack of efficacy of rituximab in Wegener's granulomatosis with refractory granulomatous manifestations. Issue 7 (3rd November 2005) - Aries, P M; Hellmich, B; Voswinkel, J; Both, M; Nölle, B; Holl-Ulrich, K; Lamprecht, P; Gross, W L
Abstract : Objective: To investigate the safety and efficacy of rituximab (RTX) in patients with refractory Wegener's granulomatosis (WG). Patients and methods: Eight consecutive patients with active refractory WG were included. In all patients disease activity had persisted despite standard treatment with cyclophosphamide and prednisolone, as well as tumour necrosis factor α blockade 3 months before inclusion in the study. Patients had particular granulomatous manifestations like retro-orbital granulomata (n = 5), nodules of the lungs (n = 1), and subglottic stenosis (n = 2). RTX was given intravenously every 4th week in combination with the standard treatment in five patients and with methotrexate in two others. Disease extent and activity were monitored clinically by interdisciplinary care, immunodiagnostics (ANCA serology, B cells by flow cytometry), and magnetic resonance imaging. Results: Beneficial response and a reduction in disease activity were seen in three patients, two of whom went into complete remission. In three other patients, disease activity remained unchanged while the disease progressed in the remaining two patients. In all patients peripheral blood B cells fell to zero during treatment with RTX. cANCA titres remained unchanged in all except one patient. Conclusion: In this pilot study, B lymphocyte depletion was not associated with a change of the ANCA titres or obvious clinical improvement of refractory granulomatous disease in patients with WG. Further studies are needed to evaluate the role of RTX in WG.